Chip formation and similarity in the plano-grinding of explosive surrogates. (October 2018) - Jackson, Mark J; Nelson, Jameson K; Whitfield, Michael D; Morrell, Jonathan S; Handy, Rodney G; Schmidt, Peter L
The processing of polymer-bonded explosives is not widely reported in the literature, especially the machining of explosive surrogates in the combined planing and grinding operation known as plano-grinding. The process of machining long pieces of an inert substitute using a wax binder to hold sugar particles together and then subjecting the surrogate material to a linear cutting motion to generate chip fragments is described. The aim and purpose of this work is to analyze the machining of explosive surrogates in terms of chip formation models (oscillating and stress ratio models) and similarity models (chip compression ratio, Poletica, and Peclet numbers). The analysis of machining is compared to standard engineering materials so that the explosives engineer can benchmark machining performance of explosive surrogates to standard materials. The article concludes with statements on how to improve the understanding of machining of explosive surrogates with specifically engineered abrasive cutting tools.